2010
DOI: 10.1111/j.1440-1584.2010.01127.x
|View full text |Cite
|
Sign up to set email alerts
|

Urban–rural differences in psychiatric rehabilitation outcomes

Abstract: For rural communities the improvement in rehabilitation outcomes might be attributable to a more benign form of the illness and the availability of higher levels of social capital.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…Higher rates of suicide in rural compared to urban areas (Qi et al, 2014), despite protective factors such as higher social supports (Tirupati et al, 2010; Yoshimasu et al, 2008), in addition to differential rates of suicide by migrant, indigenous and socioeconomic status (Law et al, 2016; Page et al, 2006; Qi et al, 2012; Too et al, 2018), suggests the potential role of mental health service availability and access as an important modifiable factor in preventing suicide (Korosec Jagodic et al, 2013). Successive suicide prevention frameworks and action plans have called for improvements to the availability, quality and integration of mental health services and enhancement of workforce capacity, which continues under current mental health reforms (Department of Health, 2009, 2012, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Higher rates of suicide in rural compared to urban areas (Qi et al, 2014), despite protective factors such as higher social supports (Tirupati et al, 2010; Yoshimasu et al, 2008), in addition to differential rates of suicide by migrant, indigenous and socioeconomic status (Law et al, 2016; Page et al, 2006; Qi et al, 2012; Too et al, 2018), suggests the potential role of mental health service availability and access as an important modifiable factor in preventing suicide (Korosec Jagodic et al, 2013). Successive suicide prevention frameworks and action plans have called for improvements to the availability, quality and integration of mental health services and enhancement of workforce capacity, which continues under current mental health reforms (Department of Health, 2009, 2012, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Suicide rates are higher in rural than in urban regions (11,12), despite higher social support (13), which is considered a protective socioeconomic factor against suicide (14). This could be explained by lower availability of psychiatric services in rural regions (15,16).…”
mentioning
confidence: 99%
“…Presumably, the structure and habits of a rural community may allow for some patients to function quite satisfactory in this context despite the partial remitted symptomatology. Notably, it has been suggested that the availability and access to the so-called social capital in the form of family support may also play significant role in outcomes for the rural residents with psychotic disorders (Tirupati et al, 2010). Moreover, there is some evidence that rural inhabitants may have a more positive attitude towards mental illness (Mutiso et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Less is known about the outcome of patients with psychotic disorders in rural areas. Interestingly, in a comparative study in Australia, Tirupati, Conrad, Frost, and Johnston (2010) found that the outcome of rehabilitation intervention for chronic severe mental disorders was better in the rural residents than in those living in urban areas. More recently, Yang et al (2015) examined marriage as the primary outcome in urban and rural residents with schizophrenia in China.…”
Section: Introductionmentioning
confidence: 99%